A centralidade do trabalho e a Indústria Cultural: impactos no envelhecimento ( The centrality of work and the Cultural Industry: impacts on aging) Doi: 10.5212/Emancipacao.v.16i2.0009 - Teixeira, Laís Vila Verde; Oliveira, Josiani Julião Alves de (Emancipação, 2017)
Resumo: O presente artigo busca analisar os impactos da Indústria Cultural na sociedade contemporânea. Trazemos uma explanação sobre a categoria trabalho e sua forma de organização na sociedade capitalista. O envelhecimento não se desvencilha da questão do trabalho visto que, hoje temos muitas pessoas idosas ativas no mercado mesmo depois de se aposentarem, muitas vezes por não encontrarem respaldo nas políticas sociais voltadas para a velhice. A Indústria Cultural também atinge este segmento, oferecendo produtos que levam a uma aparente satisfação pessoal diante da legitimação do uso da arte para disseminação do consumo. Este trabalho é fruto de pesquisa bibliográfica sobre as questões que envolvem o envelhecimento e a Indústria Cultural na atual organização do mundo do trabalho. Palavras-chave: Trabalho. Envelhecimento. Indústria Cultural. Abstract: This article analyzes the impacts of the Cultural Industry on contemporary society. We bring an explanation about the work category and its form of organization in capitalist society. Aging does not disengages from labor issue since because today we have many active older people in the market even after they retire, often because they do not find support in social policies geared towards old age. The Cultural Industry also affects this segment offering products that lead to an apparent personal satisfaction before the legitimizing of the use of art for the dissemination of consumption. This work is the result of bibliographical research on the issues that involve aging and the Cultural Industry in the current organization of the world of work. Keywords: Work. Aging. Cultural Industry.